2006
DOI: 10.1016/j.jcrs.2006.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Finite-element simulation of corneal applanation

Abstract: investigated the effect of corneal biomechanical properties on Goldmann applanation tonometry. Using a theoretical model, they showed that Young's modulus of the cornea (a measure of corneal rigidity) can have large effects on the measurement result. As Figure 1 shows, the Liu-Roberts model predicts deviations up to about 15 mm Hg from an assumed true intraocular pressure (IOP) of 20 mm Hg if the corneal Young's modulus varies between 0.1 and 0.9 MPa.The Liu-Roberts-model is based on an equation from Young, 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…He referred to a normal corneal thickness of about 520 μm. Later studies on adults revealed the relationship between CCT and applanation tonometry [6][7][8][9][10][11][12][13][14][15][16]. They suggested that a thick cornea would lead to overestimation of IOP, whereas a thin cornea would lead to IOP underestimation.…”
Section: Introductionmentioning
confidence: 99%
“…He referred to a normal corneal thickness of about 520 μm. Later studies on adults revealed the relationship between CCT and applanation tonometry [6][7][8][9][10][11][12][13][14][15][16]. They suggested that a thick cornea would lead to overestimation of IOP, whereas a thin cornea would lead to IOP underestimation.…”
Section: Introductionmentioning
confidence: 99%
“…The applanated corneal area exerts a nonuniform elastic reaction force [13] against the applanation surface of the cone (see Appendix 2), distributed according to the following law:…”
Section: The Force F2mentioning
confidence: 99%
“…Several researchers have already worked on the study of ocular structures to estimate the IOP after surgery . However, there is no report in these literatures to build a finite element model along with an algorithm, which embeds the tissue parameters for predicting the IOP reading after LASIK directly.…”
Section: Introductionmentioning
confidence: 99%